PENGARUH KUALITAS PRODUK DAN KENYAMANAN FISIK TERHADAP KEPUASAN PELANGGAN MELALUI PENGALAMAN PELANGGAN DI RESTORAN WE THE FORK 24 JAM - Billy Kukenzie; Michelle Calista (JURNAL ILMIAH EDUNOMIKA, 2026)
Customer satisfaction is a critical determinant of sustainability in the competitive restaurant industry, particularly for establishments operating on a 24-hour basis. This research examines the effects of product quality and physical comfort on customer satisfaction, through customer experience, at We The Fork 24-Hour Restaurant in Surabaya. A quantitative explanatory approach was employed, using data collected from 138 respondents through structured questionnaires distributed to dine-in customers. The data were analyzed using SEM-PLS to assess all 5 hypothesis. The findings indicate that product quality and physical comfort have positive and significant effects on customer experience. Furthermore, product quality, physical comfort, product quality and physical comfort have a positive and significant effects on customer satisfaction. But customer experience does not have significant effect on customer satisfaction. These results highlight the importance of maintaining consistent food quality, creating a comfortable physical environment, and delivering positive dining experiences to enhance customer satisfaction. The findings provide practical insights for restaurant managers in improving service strategies and contribute to the literature on consumer behavior in the culinary sector.